KAPASITAS FLEKURAL BALOK BETON BERTULANG DENGAN PEMBUKAAN SIRKULER DAN DETAIL PENGUATAN DI ZONA KETEGANGAN - Budi , Ghalib Setyo; Khomari , Mohamad Galuh; Pranowo , Dadang Dwi; Amin , M. Shofi’ul; Hutasoit , Eva Olivia (Teknik Sipil, Fakultas Teknik Universitas Negeri Jakarta, 2024)
The pipes placed below the beams are intended for aesthetic purposes and are subsequently covered by the ceiling, resulting in an unused space. The height of this space will always be determined by the size of the pipes installed below the beams. One alternative plan to route the piping installations above is by creating circular holes with detailing in the beams. The testing conducted in this study involved the flexural testing of beams with simple supports. The concrete beams used as the flexural test specimens were sized at (10 x 15 x 100) cm. The research results indicate that the capacity of the beams increased due to the presence of holes in the tensile and compressive areas. In terms of percentage, when compared to the control beam, the flexural capacity increased by 13% for BBTE1, 4.425% for BBTE2, 6.667% for BBTA1, and 5.607% for BBTA2. The observation of crack patterns revealed that overall failure in the beams occurred through flexural failure for beams BN, BBTE1, BBTE2, BBTA1, and shear failure for beam BBTA2.